Organometallic chemistry : a unified approach - Mehrotra, R C (New Age International, 2000)
The book is a revised edition of a lucid and stimulating introductory account of Organometallic Chemistry, an exciting and rapidly developing interdisciplinary branch of science. A characteristic feature of this book is the presentation of an integrated (covering different facets usually dealt with either in organic or/and inorganic texts) view of the rapidly developing field of organometallic chemistry. Attempts have been made to choose the latest examples to illustrate the fundamental properties as well as the synthetic procedures of organometallic chemistry. Other features include: (a) an interesting brief historical background of the subject including some quotations from relevant nobel lecture accounts of epoch making advances by the discoverers themselves, (b) the adoption as far as possible of the IUPAC rules of nomenclature, (c) a brief account of the rapidly emerging organometallic chemistry of the f-elements, and (d) inclusion of study questions at the end of each chapter.